Analisis Keamanan Website Kampus UNIPDU Melalui Metode Vulnerability Assessment (VA) dengan Menggunakan Tools Acunetix - Syaifudin, Moh Rizki; Murtadho, Mohamad Ali; Wafa, Moh Shohibul; Masrur, Mukhamad (Program Studi Teknik Informatika - Universitas Komputer Indonesia (UNIKOM), 2025)
Amidst the rapid development of technology, website vulnerabilities are a major threat, opening up opportunities for hackers to hunt and steal important data. Web applications are a technological innovation that not only facilitates access to information on the Unipdu Jombang campus, but also functions as the main link in the information system, even though they have to face major challenges in maintaining its security. By using the Vulnerability Assessment (VA) approach that utilizes Acunetix technology, this study attempts to assess the weaknesses of the Unipdu Jombang campus website and offers suggestions for improving its security. The main domain of the website is the focus of the study, which uses automated testing methodology to find vulnerabilities that could be exploited. Many vulnerabilities were found by the test results, including the use of reverse proxy detected, using cloud services such as CloudFlare, and TLS/SSL certificates that are almost expired. Through reports from scans that comply with the OWASP Top 10 2021 guidelines on Acunetix tools, 2 groups of vulnerability categories were found, including: (A05) security misconfiguration and (A06) Vulnerable and Outdated Components. It is hoped that these efforts will improve data security and thwart various threats. The results of this study provide important information for Unipdu website developers, including the need to update SSL certificates and suggest scanning on internal versions of web applications without active WAF. These findings not only strengthen system security, but also help campuses maintain user trust while also being a guide for the development of more reliable and secure information systems in the future.